2020
DOI: 10.3390/ijerph17197188
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Households’ Payment for Waste Disposal and Recycling Behaviours? Empirical Evidence from South Africa’s General Household Survey

Abstract: Safeguarding the environment and its citizens’ health remains one of the key policy priorities of the governments of many developing and emerging countries. Using the 2017 General Household Survey (GHS) dataset, this study examines the driving factors affecting households’ recycling behaviour and payment for waste disposal in South Africa. The methods of data analysis were based on descriptive statistics and a Bivariate Probit regression model. The descriptive statistics results indicate that there are 56.29% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 66 publications
2
10
0
Order By: Relevance
“…Most (54.90%) of the respondents indicated that they removed wastes through self-efforts. This supports the assertion that rapid population growth is uncontrollably causing social and environmental strains in the developing nations of the world, and the magnitude of this challenge is reflected by the increasing amount of solid and liquid waste generated and deposited [39]. Consequently, common features of developing nations such as South Africa are massive areas with stinking heaps of uncollected waste disposed carelessly by roadsides and open spaces which are sometimes borne out of noncompliance to waste disposal rules and improper facilities.…”
Section: Environmental and Infrastructuralchracteristics Of Ezakheleni Informal Settlementsupporting
confidence: 63%
See 2 more Smart Citations
“…Most (54.90%) of the respondents indicated that they removed wastes through self-efforts. This supports the assertion that rapid population growth is uncontrollably causing social and environmental strains in the developing nations of the world, and the magnitude of this challenge is reflected by the increasing amount of solid and liquid waste generated and deposited [39]. Consequently, common features of developing nations such as South Africa are massive areas with stinking heaps of uncollected waste disposed carelessly by roadsides and open spaces which are sometimes borne out of noncompliance to waste disposal rules and improper facilities.…”
Section: Environmental and Infrastructuralchracteristics Of Ezakheleni Informal Settlementsupporting
confidence: 63%
“…This indicates that respondents' working experience had a strong positive relationship with their living conditions in the study area. This is expected as households are more likely to make more income to improve their living conditions when they have more years of working experience [39,56]. In the same vein, the households' food security status parameter had a significant (p < 0.05) and positive (0.1175769) effect on their living conditions.…”
Section: Estimates Of Factors Contributing To the Households' Living Condition In The Study Areamentioning
confidence: 88%
See 1 more Smart Citation
“…This is a significant issue for municipalities as the financial costs associated with addressing the environmental and health impacts of littering and illegal dumping are higher than the cost of developing and operating cost-effective and adequate waste management systems [19]. Littering is a major environmental problem and previous research confirms that households perceive littering and dumping of waste as an environmental problem that requires measures for control or eradication [46]. Our research emphasizes that socio-economic factors affect how households address their waste practices.…”
Section: Discussionmentioning
confidence: 99%
“…Arbués and Villanúa (2016) also adopt a related approach, but these authors focus on environmental concern rather than personal norms as an endogenous determinant of, in their case, households' recycling of batteries Omotayo et al (2020). consider the endogenous relationship between household recycling and the payment for waste disposal.…”
mentioning
confidence: 99%